Signal Pathway of Estrogen and Estrogen Receptor in the Development of Thyroid Cancer - Liu, Jian; Xu, Tianmin; Ma, Li; Chang, Weiqin (Frontiers in Oncology, 2021)
The molecular mechanisms underlying the development of thyroid cancer (TC) have been examined through extensive experiments. A large number of studies have shown that the incidences of thyroid cancer in women is much higher than that in men, so estrogen plays a key role in the development of thyroid cancer. Estrogen plays its growth-promoting role through classical genomic and non-genomic pathways mediated by membrane-bound estrogen receptors. We summarize the understanding of molecular mechanisms of estrogen signaling pathways in thyroid cancer. Furthermore, it will provide a new target for the treatment of thyroid carcinoma by blocking estrogen and its related action pathway.